PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - AYU DWI LESTARI, DYAH; DUDY SETYAWAN, MADE (Jurnal Akuntansi AKUNESA, 2018)
ABSTRACTKnowledge-based industry, competing by using innovation as the creation of its own value for products or services. The banking and insurance industry is an industry that utilizes the knowledge and human resources that are owned to create innovations to create value for the products or services produced. This study aims to determine the effect of intellectual capital on firm value and determine the effect of intellectual capital on firm value by using profitability as a moderating variable. The sample uses banking and insurance companies listed on the Indonesia Stock Exchange (IDX) for the 2013-2016 period. Analysis of research data with Moderated Regression Analysis. The results of the study show that intellectual capital has an effect on company value and profitability can moderate the relationship between intellectual capital and firm value.Keywords: Intellectual Capital, Firm Value, Profitability